2021
DOI: 10.1159/000519373
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Biomarkers Predicting Visual Acuity Change after Intravitreal Bevacizumab Injections for Macular Edema Secondary to Branch Retinal Vein Occlusion

Abstract: <b><i>Purpose:</i></b> This study aimed to identify baseline optical coherence tomography (OCT) factors in branch retinal vein occlusion (BRVO) that predict response to bevacizumab injections. <b><i>Methods:</i></b> It is a retrospective case series of consecutive patients that underwent OCT at diagnosis, and the central macular thickness (CMT), extent of disorganized retinal inner layers, and outer retinal layers including external limiting membrane, ellipsoid z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…We believe that this might be attributed to prolonged retinal and ME in eyes with longer disease duration, as prolonged edema can result in irreversible retinal damage [16] and more severe visual impairment, thereby increasing the likelihood of poor visual prognosis post-treatment. Another investigation revealed a correlation between poorer pre-treatment BCVA and worse visual recovery post-treatment [17]. Our results demonstrated that patients' eyes in the poor prognosis group had significantly lower pre-treatment BCVA compared to those in the good prognosis group and was an independent risk factor for BRVO-ME eye prognosis following ranibizumab treatment, indicating the importance of early intervention in BRVO-ME eyes during treatment to enhance BCVA for improved prognosis.…”
Section: Discussionmentioning
confidence: 49%
“…We believe that this might be attributed to prolonged retinal and ME in eyes with longer disease duration, as prolonged edema can result in irreversible retinal damage [16] and more severe visual impairment, thereby increasing the likelihood of poor visual prognosis post-treatment. Another investigation revealed a correlation between poorer pre-treatment BCVA and worse visual recovery post-treatment [17]. Our results demonstrated that patients' eyes in the poor prognosis group had significantly lower pre-treatment BCVA compared to those in the good prognosis group and was an independent risk factor for BRVO-ME eye prognosis following ranibizumab treatment, indicating the importance of early intervention in BRVO-ME eyes during treatment to enhance BCVA for improved prognosis.…”
Section: Discussionmentioning
confidence: 49%
“…In RVO, optical coherence tomography (OCT) has been widely used to assess the presence and the extent of ME, subretinal fluid (SRF), cotton wools, and hard exudates 64,65. Studies have shown that while SRF is common at presentation, baseline SRF is not a predictor of functional or anatomic results long-term 66,67…”
Section: Clinical Diagnosis and Multimodal Imagingmentioning
confidence: 99%
“…64,65 Studies have shown that while SRF is common at presentation, baseline SRF is not a predictor of functional or anatomic results long-term. 66,67 Assessing the amount and duration of ME is important, as a shorter duration has been associated with better outcomes in BRVO. 68 The junction between the inner and the outer segments of the photoreceptors is particularly important as its integrity is fundamental for the visual prognosis.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%